Seakeeping Analysis of Floating Structures with Pipe Integration Based on the Boundary Element Method - Onyshchenko, Svitlana; Faizatama, Alfido Marchandi; Firdaus, Nurman; Adiputra, Ristiyanto (Universitas Sebelas Maret, 2025)
Floating structures are key components in offshore renewable energy systems. In the development of energy conversion, several integrated components are required, one of which is the Cold-Water Pipe (CWP). This integration will affect the interaction of the structure with environmental loads such as waves and currents, which influence the stability and seakeeping of the structure. This study employs computational analysis based on the Boundary Element Method (BEM) to more efficiently evaluate the hydrodynamic response of full-scale structures. Response Amplitude Operator (RAO), additional mass, motion response, and mooring line tension are identified as the main parameters. It was found that all these parameters are sensitive to mesh discretization. A mesh convergence study was conducted using mesh sizes of 1.8, 2.1, 2.2, and 2.3 m, which produced consistent RAO and additional mass values. Conversely, mesh sizes of 1.9, 2.0, 2.4, and 2.5 m showed inconsistencies in stability results at sea. The coarsest net (2.5 m) produced errors of up to 33% in swing, heave, and roll motions, with greater deviations in heave motion. However, tension on the mooring line remained relatively stable, indicating reduced sensitivity to variations in net size.